Respuesta :
If 7m-3=53, them 7m=53+3
7m = 56, so m = 8.
Plug this into the other equation, 11m+2.
11(8) + 2 = 88 + 2 = 90
7m = 56, so m = 8.
Plug this into the other equation, 11m+2.
11(8) + 2 = 88 + 2 = 90
Step-by-step explanation:
It is given that,
7m - 3 = 53.... (1)
Firstly, we need to find the value of m and then solving the equation, 11m + 2
From equation (1),we can find the value of m. When 3 moves to right hand side it becomes positive as
7m = 53 + 3
7m = 56
[tex]m=\dfrac{56}{7}[/tex].......(2)
Put the value of m from equation (2) in 11m +2
This gives, [tex]11\times \dfrac{56}{7}+2[/tex]
m = 90
So, the value of 11 m +2 is 90